2017
DOI: 10.1155/2017/1728345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surfactant on Growth of ZnO Nanodumbbells and Their Characterization

Abstract: We report the controlled synthesis of dumbbell shaped ZnO micro/nanostructures using anionic surfactant sodium dodecyl sulphate (SDS) by simple one-step hydrothermal method. The morphology changes of ZnO were characterized by using scanning electron microscopy, X-ray diffraction, and energy dispersive spectroscopy. It is found that the size of the dumbbell increased with increase in concentration of SDS. Systematic growth mechanism with increase of concentration of SDS polymer is studied. Our results will help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This chemistry was reported to be responsible for the surface-controlled defect potentials of ZnO [41]. In a similar way, for the ZnO-SDS sample, some studies reported the effectiveness of SDS in the formation of a bare crystalline phase by acting as a growth template in the functionalization of ZnO NPs [42]. Since SDS has S=O groups that could act as proton receptors, and, in aqueous solution, they ionize into Na + (S) and CH 3 (CH 2 ) 11 OSO 3 − (DS − ).…”
Section: Physicochemical Characterization Of Surface-modified Zno Npsmentioning
confidence: 63%
See 1 more Smart Citation
“…This chemistry was reported to be responsible for the surface-controlled defect potentials of ZnO [41]. In a similar way, for the ZnO-SDS sample, some studies reported the effectiveness of SDS in the formation of a bare crystalline phase by acting as a growth template in the functionalization of ZnO NPs [42]. Since SDS has S=O groups that could act as proton receptors, and, in aqueous solution, they ionize into Na + (S) and CH 3 (CH 2 ) 11 OSO 3 − (DS − ).…”
Section: Physicochemical Characterization Of Surface-modified Zno Npsmentioning
confidence: 63%
“…Since SDS has S=O groups that could act as proton receptors, and, in aqueous solution, they ionize into Na + (S) and CH 3 (CH 2 ) 11 OSO 3 − (DS − ). The formed ions in contact with the polar faces of ZnO reduce its surface defects and facilitate the formation of small crystalline particles [42]. Ahson et al (2020) observed that the hydrothermal growth with SDS favored the formation of small crystalline ZnO NPs, i.e., the bare polar planes of ZnO favor the formation of more oxygen vacancies [43].…”
Section: Physicochemical Characterization Of Surface-modified Zno Npsmentioning
confidence: 99%
“…EADI et al reported that SDS has a positive effect on the crystallinity of ZnO powders. In this procedure, (SO 4 2-) unit was absorbed to the (0001) face of ZnO from a nut-like structure and the (SO 4 2-) unit was sandwiched between two (0001) faces and ZnO crystal growth happened along (0001) faces [44]. The difference between the pattern of PEG-70 and other samples could be due to the presence of the Zn(OH) 2 along with ZnO [41].…”
Section: Structural Analysismentioning
confidence: 99%
“…Alammar et al have studied the effect of five different ILs on ZnO morphologies, and claimed that the habitus and morphology come as the system naturally tends to reduce the total surface energy during formation; it is to note that the anion of the IL is proposed to be interacting with the ZnO surface during the growth [134]. Yet, the best performance was for ZnO nanoparticles that are obtained by use of IL with a long alkyl chain, reaching 95% in 9 h for methyl orange decomposition, proposing that along with high surface area, oxygen vacancies and polar plans that act like electron traps are the main factors for such interesting photocatalytic activity [135,136]. It was also reported by Amde et al [137] that common techniques for the determination of fungicide concentration in water are usually non-environmentally friendly, organic solvent, and time consuming; the group has prepared ZnO nanofluids by a green two-step method, dispersing the as-synthesized sol-gel ZnO nanoparticles in 1-hexyl-3-methylimidazolium hexafluorophosphate, hand shaking it to attain a homogeneous distribution, then sonicating it to break NPs clusters.…”
Section: Ionic Liquid As Solvents For Zno Nanostructuresmentioning
confidence: 99%